Pengembangan LKPD Berbasis STEM (Science, Technology, Engineering, Mathematic) Pada Materi Elastisitas Dan Hukum Hooke - Reihan Laila Shabila; Yoga Budi Bhakti; Fatahillah Fatahillah (UNIVERSITAS INDRAPRASTA PGRI, 2020)
The development of STEM-based LKPD (Science, Technology, Engineering, and Mathematics ) was carried out because it saw the conditions in the field for class XI students of SMA PGRI Depok. The objectives of this research were: To find out how feasible STEM-based LKPD (Science, Technology, Engineering, and Mathematics) On the Material of Elasticity and Hooke's Law. As well as to find out the characteristics of STEM-based LKPD (Science, Technology, Engineering, and Mathematics) on Elasticity and Hooke's Law. In general. The data collection techniques used in this study were interviews and literature studies. The validity of this instrument was using instrument testing. The results of the validation of the feasibility instrument trial of the language at LKPD obtained a maximum score of 87.5% with an average score of 77, 5% while the results of the instrument trial validation the feasibility of the material obtained a maximum score of 100% with a good interpretation and with the same average as the validation of language feasibility, which according to media experts is said to be good and worthy of being tested.